Elesesterpenes A–K: Lupane-type Triterpenoids From the Leaves of Eleutherococcus sessiliflorus - Han, Dong; Liu, Yan; Li, Xiao-Mao; Wang, Si-Yi; Sun, Yan; Algradi, Adnan Mohammed; Zou, Hai-Dan; Pan, Juan; Guan, Wei; Kuang, Hai-Xue; Yang, Bing-You (Frontiers in Chemistry, 2022)
Elesesterpenes A-K (1-11), eleven new lupane-type triterpenoids, triterpenoid glycosides, and nortriterpenoid, were isolated from the leaves of Eleutherococcus sessiliflorus. Their structures and relative configurations were completely elucidated by a combination of diverse methods including physical, spectroscopic data. The absolute configuration of elesesterpenes A-B (1-2) was defined by single-crystal X-ray diffraction. Meanwhile, all the isolates were evaluated for anti-inflammatory activities on lipopolysaccharide-induced nitric oxide production in BV2 microglial cells, and anti-proliferative activities against human hepatoma (HepG2), human lung adenocarcinoma (A549), and human glioma cells (LN229) in vitro. It was found that some of them exhibited obvious anti-inflammatory activities and potent anti-proliferative activities.